PREVALENCE AND HEALTH FACILITY FACTORS ASSOCIATED WITH ABNORMAL VAGINAL DISCHARGE AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT WAKISO HEALTH CENTER IV, WAKISO DISTRICT – A CROSS-SECTIONAL STUDY. - Muyomba , Martin; Mukirya , Namaasa Aeron (Student's Journal of Health Research Africa, 2025)
Introduction Abnormal vaginal discharge (AVD) increases the risk of sexually transmitted infections (STIs) and adverse pregnancy outcomes. This study purposed to determine the prevalence and health facility factors associated with abnormal vaginal discharge among pregnant women attending antennal care at Wakiso Health Center IV, Wakiso District in Central Uganda. Methods A cross-sectional study was conducted on 100 participants, selected by systematic random sampling. A structured questionnaire with closed-ended questions and a data extraction form were used for data collection. The data was analyzed in SPSS v.21 using mean, frequencies, percentages, chi-square, and binary logistic regression. Participants provided written informed consent for participation. Ethical approval was sought from the College Research and Scientific Committee and administrative clearance was obtained from the District Health Office and the Health Facility In-Charge. Results Data was collected from 100 participants with a mean age of 31.9 (S = 7.63) years. The prevalence of abnormal vaginal discharge was 40% and significant health facility factors were perceived quality of antenatal care services (aOR=8.001; 95% CI: 1.31 – 33.157; p-value = 0.004), distance to the health facility (aOR=12.956; 95% CI: 1.902 – 88.272; p-value = 0.009), and provision of a friendly care environment (aOR=5.889; 95% CI: 1.335 – 25.976; p-value = 0.019). Conclusion The prevalence of abnormal vaginal discharge among pregnant women attending antenatal care at Wakiso Health Center IV is high and is associated with the perceived quality of antenatal care, distance to health facilities, and provision of a friendly care environment. Recommendations There is a need for health workers to motivate pregnant women to seek timely care and provide during pregnancy and provide a friendly environment for prompt and effective treatment of abnormal vaginal discharge in pregnancy.